Adjusting the legal text and its impact on the differences of jurists - Abu Yahya, Ali (Jordan Journal of Islamic Studies, 2023)
The difference of jurists existed from the era of prophet hood, and passing through the era of the Companions and those who followed to our days. This jurisprudential difference has many and varied reasons, and the difference in controlling the legal text is one of these reasons. This study aims to clarify, study and highlight this topic, by controlling the concept of the legal text, explaining the reasons for the difference due to controlling the text and listing some examples of jurisprudential issues, in which the difference in controlling the text had an effect on the occurrence of disagreement among the jurists in it, leading to the conclusion that comes from Its most important results: The difference in controlling the legal text is in the Qur’an, through the different readings among the readers. The occurrence of disagreement in controlling the text in the purified Sunnah of the Prophet, and among its forms is insertion and replacement of the word with its synonym and increased confidence …. among other reasons, most of which refer to the narration of the hadith in the meaning. The difference in controlling the legal text had an effect on the occurrence of the jurisprudential dispute, as it was one of the reasons for the disagreement of the jurists in general.